Fluorine-indium co-doped lithium manganese iron phosphate positive electrode material and preparation method thereof
By introducing fluorine and indium into the lithium manganese iron phosphate positive electrode material, a co-doped structure is formed, and the problem of insufficient conductivity and stability of the material is solved through high-energy ball milling and carbon coating technology, and the battery energy density and cycling stability are significantly improved.
Patent Information
- Application Number
- CN202310393437.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-04-13
AI Technical Summary
Lithium manganese iron phosphate positive electrode material has poor conductivity and stability in lithium-ion batteries, resulting in insufficient energy density and cyclic stability, hindering its industrialization development.
By introducing a small amount of fluorine and indium sources into the lithium manganese iron phosphate material, a fluorine indium co-doped structure is formed, and the conductivity and structural stability of the material are improved by using high-energy ball milling and carbon coating technology.
The battery energy density and reversible specific capacity of the fluorine indium fluorine-doped lithium manganese iron phosphate positive electrode material have been significantly improved, and the cycle stability and rate performance have been improved.
Smart Images

Figure CN116514088B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium-ion battery technology and relates to a fluorine-indium co-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] Since it was first proposed in 1997, the LiFePO4 cathode material with an olivine structure has received great attention from the lithium-ion battery industry. Compared with ternary cathode materials, lithium iron phosphate has excellent cycle performance, thermal stability and safety. The reason is that the PO covalent bonds contained in it can stabilize and strengthen the material's own structure, making Fe 2+ / Fe 3+ The olivine structure can still be maintained during the redox process. However, the discharge voltage platform of lithium iron phosphate cathode materials is relatively low (3.4V), and its actual battery energy density is close to the limit, which cannot meet people's application needs for long-term battery life. Therefore, improving the energy density of lithium iron phosphate series cathode materials has become a hot topic in recent years.
[0003] Recent studies have shown that by incorporating manganese into the lithium iron phosphate lattice to obtain lithium manganese iron phosphate, its discharge voltage platform is higher (4.1V); compared with lithium iron phosphate, the positive electrode energy density of lithium manganese iron phosphate is increased by about 20%. In addition, due to the close ionic radius of divalent manganese ions (0.083nm) and divalent iron ions (0.078nm), iron and manganese elements can be mutually dissolved in any proportion without affecting the original olivine structure. However, when used as the positive electrode of lithium-ion batteries, the electronic conductivity and ionic conductivity of the lithium manganese iron phosphate material itself are poor. If the proportion of manganese introduced is not appropriate, the lithium manganese iron phosphate will experience rapid decline in specific capacity and poor cycle stability due to the John-Teller effect caused by manganese. The above defects have seriously hindered the industrial development and application of lithium manganese iron phosphate positive electrodes. The currently widely used technology is mainly to use carbon or conductive polymer coating to enhance the conductivity and stability of lithium manganese iron phosphate, but its effect is limited. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a fluorine-indium co-doped lithium iron manganese phosphate positive electrode material and a preparation method thereof, so as to improve the electrochemical properties of lithium iron manganese phosphate by doping and modifying the lithium iron manganese phosphate material.
[0005] To achieve the above object, the technical solution provided by the present invention is as follows:
[0006] The present invention discloses a method for preparing a fluorine-indium co-doped lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0007] (1) adding a lithium source, an iron source, a manganese source, a phosphorus source, a fluorine source, an indium source, a carbon source and a grinding aid into a ball mill to perform high-energy ball milling; (2) drying and grinding the ball milled wet sample to obtain a precursor;
[0008] (3) The precursor is placed in an inert atmosphere for calcination to obtain a carbon-coated fluorine-indium co-doped lithium manganese iron phosphate positive electrode material.
[0009] As a preferred technical solution, in the step (1), the lithium source, iron source, manganese source, phosphorus source, fluorine source and indium source are configured according to the molar ratio of Li, Fe, Mn, P, F and In of 1:0.5:0.49:1:0.005~0.05:0.003~0.03.
[0010] As a preferred technical solution, in the step (1), the lithium source, iron source, manganese source, phosphorus source, fluorine source and indium source are configured according to the molar ratio of Li, Fe, Mn, P, F and In of 1:0.5:0.49:1:0.03:0.01.
[0011] As a preferred technical solution, in step (1), the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium fluoride, and the iron source is one or more of ferrous oxalate, ferrous oxide, ferric phosphate, and ferric fluoride.
[0012] As a preferred technical solution, in step (1), the manganese source is one or more of manganese oxalate, manganese carbonate, and manganese acetate, and the phosphorus source is one or more of iron phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate.
[0013] As a preferred technical solution, in step (1), the fluorine source is one or more of ammonium fluoride, lithium fluoride, and ferric fluoride, and the indium source is one or more of indium sulfide, indium oxide, and indium phosphide.
[0014] As a preferred technical solution, in step (1), the grinding aid is one or more of anhydrous ethanol, acetone, and ethylene glycol.
[0015] As a preferred technical solution, in step (1), the carbon source is glucose or sucrose, and the amount of the carbon source added is 5 to 20% of the total mass of the calcined raw material.
[0016] As a preferred technical solution, in step (3), the calcination conditions are: a heating rate of 10°C / min; the calcination is divided into two stages, the calcination temperature of the first stage is 300-350°C, and the calcination time is 1-4h; the calcination temperature of the second stage is 600-700°C, and the calcination time is 10-15h.
[0017] The invention also discloses a fluorine-indium co-doped lithium manganese iron phosphate positive electrode material prepared by the preparation method.
[0018] The beneficial effects of the present invention are:
[0019] The present invention introduces a small amount of fluorine source and indium source during the preparation process of the carbon-coated lithium manganese iron phosphate positive electrode material, thereby obtaining a positive electrode material based on lithium manganese iron phosphate with a stable structure and enhanced conductivity. Fluorine and indium replace part of the oxygen and manganese elements in the lithium manganese iron phosphate lattice structure respectively. Due to the different doping substitution positions, the two ions have a synergistic effect, and the co-doping effect on the improvement of the conductivity of lithium manganese iron phosphate is better than the doping effect of a single ion. When the fluorine-indium co-doped lithium manganese iron phosphate is used for the positive electrode of a lithium-ion battery, the battery energy density and reversible specific capacity can be significantly improved.
[0020] The method of the present invention is easy to operate and can be achieved by adding a certain proportion of manganese source, fluorine source and indium source to the original lithium iron phosphate production line equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:
[0022] Figure 1 This is a SEM image of the fluorine-indium co-doped lithium manganese iron phosphate prepared in Example 1 of the present invention.
[0023] Figure 2 This is the XRD diagram of the fluorine-indium co-doped lithium manganese iron phosphate prepared in Example 1 of the present invention.
[0024] Figure 3 It is a comparison diagram of the charge and discharge curves of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention at a current density of 0.1C.
[0025] Figure 4 It is a comparison chart of the rate test results of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0026] Figure 5 It is a comparison chart of the cycle test results of Example 1, Example 2 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present invention will be described in detail below in conjunction with the embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments, and the scope of the present invention should not be interpreted as being limited to the embodiments described below. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] Lithium carbonate, ferrous oxalate dihydrate, manganese oxalate, ammonium dihydrogen phosphate, ammonium fluoride, indium sulfide and 16% of the total solid mass of glucose were added to ethanol according to the molar ratio of Li, Fe, Mn, P, F, In of 1:0.5:0.49:1:0.03:0.01, and high-energy ball milling was performed for 13 hours. The ball-milled sample was placed in an oven for drying, and then ground to obtain a precursor powder. The precursor powder was moved to a tubular furnace protected by an argon atmosphere, heated to 350°C at a heating rate of 10°C / min, kept warm for 3 hours, and then heated to 650°C at a heating rate of 10°C / min, kept warm for 10 hours, and then cooled to room temperature, and ground to obtain a carbon-coated fluorine-indium co-doped lithium manganese iron phosphate positive electrode material.
[0030] Example 2
[0031] Lithium carbonate, ferric oxide, manganese acetate tetrahydrate, ammonium dihydrogen phosphate, ammonium fluoride, indium sulfide and 19% of the total solid mass of sucrose were added to acetone according to the molar ratio of Li, Fe, Mn, P, F, and In of 1:0.5:0.49:1:0.03:0.01, and high-energy ball milling was performed for 13 hours. The ball-milled sample was placed in an oven for drying, and then ground to obtain a precursor powder. The precursor powder was moved to a tube furnace protected by an argon atmosphere, heated to 350°C at a heating rate of 10°C / min, kept warm for 3 hours, and then heated to 650°C at a heating rate of 10°C / min, kept warm for 10 hours, and then cooled to room temperature, and ground to obtain a carbon-coated fluorine-indium co-doped lithium manganese iron phosphate positive electrode material.
[0032] Comparative Example 1
[0033] Lithium carbonate, ferrous oxalate dihydrate, manganese oxalate, ammonium dihydrogen phosphate, indium sulfide and 16% of the total solid mass of glucose were added to ethanol according to the molar ratio of Li, Fe, Mn, P and In of 1:0.5:0.49:1:0.01, and high-energy ball milling was performed for 13 hours. The ball-milled sample was placed in an oven for drying, and then ground to obtain a precursor powder. The precursor powder was moved to a tubular furnace protected by an argon atmosphere, heated to 350°C at a heating rate of 10°C / min, kept warm for 3 hours, and then heated to 650°C at a heating rate of 10°C / min, kept warm for 10 hours, and then cooled to room temperature, and ground to obtain a single indium element doped carbon-coated lithium manganese iron phosphate positive electrode material.
[0034] Comparative Example 2
[0035] Lithium carbonate, ferrous oxalate dihydrate, manganese oxalate, ammonium dihydrogen phosphate and 16% of the total solid mass of glucose were added to ethanol according to the molar ratio of Li, Fe, Mn and P of 1:0.5:0.5:1, and high-energy ball milling was performed for 13 hours. The ball-milled sample was placed in an oven for drying, and then ground to obtain a precursor powder. The precursor powder was moved to a tubular furnace protected by an argon atmosphere, heated to 350°C at a heating rate of 10°C / min, kept warm for 3 hours, and then heated to 650°C at a heating rate of 10°C / min, kept warm for 10 hours, and then cooled to room temperature and ground to obtain an undoped carbon-coated lithium manganese iron phosphate positive electrode material.
[0036] Comparative Example 3
[0037] Lithium carbonate, ferrous oxalate dihydrate, manganese oxalate, ammonium dihydrogen phosphate, ammonium fluoride and 14% of the total solid mass of glucose were added to ethanol according to the molar ratio of Li, Fe, Mn, P, and F of 1:0.5:0.5:1:0.015, and high-energy ball milling was performed for 13 hours. The ball-milled sample was placed in an oven for drying, and then ground to obtain a precursor powder. The precursor powder was moved to a tubular furnace protected by an argon atmosphere, heated to 350°C at a heating rate of 10°C / min, kept warm for 3 hours, and then heated to 650°C at a heating rate of 10°C / min, kept warm for 10 hours, and then cooled to room temperature, and ground to obtain a single fluorine-doped carbon-coated lithium manganese iron phosphate positive electrode material.
[0038] Taking the fluorine-indium co-doped lithium manganese iron phosphate prepared in Example 1 as a representative, its particles were characterized:
[0039] Figure 1 This is a SEM image of the fluorine-indium co-doped lithium manganese iron phosphate prepared in Example 1. It can be observed that it has a uniform morphology, presents a spherical shape, and has a diameter of about 100 nm.
[0040] Figure 2 This is the XRD pattern of the fluorine and indium co-doped lithium manganese iron phosphate prepared in Example 1. The diffraction peaks in the figure correspond to the standard peaks of lithium manganese iron phosphate in the PDF card (PDF#42-0580).
[0041] The lithium iron manganese phosphate of all the above embodiments and comparative examples is used as the active material of the lithium ion battery positive electrode material, conductive carbon black is used as the conductive agent, polyvinylidene fluoride PVDF is used as the binder, the three substances are mixed in a weight ratio of 8:1:1 to form an electrode sheet, and metallic lithium is used as the negative electrode, lithium hexafluorophosphate is used as the electrolyte, and polypropylene is used as the diaphragm to be assembled into a button battery.
[0042] Figure 3The charge and discharge curves of the three samples of Example 1, Comparative Example 1 and Comparative Example 2 at a current density of 0.1C are compared. According to the test results, the reversible capacity of the fluorine-indium co-doped lithium manganese iron phosphate of Example 1 can reach 140.7 mAh / g, which is higher than 128.6 mAh / g of indium-doped lithium manganese iron phosphate of Comparative Example 1 and 120.5 mAh / g of lithium manganese iron phosphate of Comparative Example 2.
[0043] Figure 4 The figure is a comparison chart of rate tests at different current densities for three samples of Example 1, Comparative Example 1 and Comparative Example 2. According to the test results, it can be seen that Example 1 co-doped with fluorine and indium has better rate performance than Comparative Example 1 doped with indium alone and Comparative Example 2 without doping.
[0044] Figure 5 The long cycle test comparison diagram of three samples of Example 1, Example 2 and Comparative Example 3. It can be found that the material of Example 1 has a more excellent long cycle performance, and the specific capacity fluctuates less and decays slowly during the cycle.
[0045] The above embodiments are only used to illustrate the preferred implementation modes of the present invention, rather than to limit the concept and protection scope of the present invention. Any modifications, equivalent substitutions and improvements made within the concept and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a fluorine-indium co-doped lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: (1) adding a lithium source, an iron source, a manganese source, a phosphorus source, a fluorine source, an indium source, a carbon source and a grinding aid into a ball milling tank for high-energy ball milling; (2) drying and grinding the ball mill wet sample to obtain a precursor; (3) calcining the precursor in an inert atmosphere to obtain a carbon-coated fluorine-indium co-doped lithium manganese iron phosphate positive electrode material; In the step (1), a lithium source, an iron source, a manganese source, a phosphorus source, a fluorine source, and an indium source are prepared according to a molar ratio of Li, Fe, Mn, P, F, and In of 1:0.5:0.49:1:0.005-0.05:0.003-0.03; In the step (3), the calcination conditions are: a heating rate of 10°C / min; the calcination is divided into two stages, the calcination temperature of the first stage is 300-350°C, and the calcination time is 1-4h; the calcination temperature of the second stage is 600-700°C, and the calcination time is 10-15h.
2. The method for preparing the fluorine-indium co-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step (1), a lithium source, an iron source, a manganese source, a phosphorus source, a fluorine source, and an indium source are configured according to a molar ratio of Li, Fe, Mn, P, F, and In of 1:0.5:0.49:1:0.03:0.
01.
3. The method for preparing the fluorine-indium co-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium fluoride, and the iron source is one or more of ferrous oxalate, ferrous oxide, ferric phosphate, and ferric fluoride.
4. The method for preparing the fluorine-indium co-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the manganese source is one or more of manganese oxalate, manganese carbonate, and manganese acetate, and the phosphorus source is one or more of iron phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate.
5. The method for preparing the fluorine-indium co-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the fluorine source is one or more of ammonium fluoride, lithium fluoride, and ferric fluoride, and the indium source is one or more of indium sulfide, indium oxide, and indium phosphide.
6. The method for preparing the fluorine-indium co-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the grinding aid is one or more of anhydrous ethanol, acetone, and ethylene glycol.
7. The method for preparing the fluorine-indium co-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the carbon source is glucose or sucrose, and the amount of the carbon source added is 5 to 20% of the total mass of the calcined raw material.
8. Fluorine-indium co-doped lithium manganese iron phosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Lithium iron manganese phosphate cathode material and preparation method thereof
CN111564622A
Preparation method of lithium manganese iron phosphate, positive electrode material and lithium ion battery
CN114644328A